Efectividad del tratamiento mediante la técnica quirúrgica mipo y convencional en fracturas de diáfisis de húmero en pacientes entre los 18 a 65 años en el Hospital IV Víctor Lazarte Echegaray - Quevedo Avila, Jonathan Manuel (2020)
Purpose of the study: Being humerus fractures one of the most frequent in long bones and in young patients, and currently of surgical indication using conventional technique or MIPO, it is important to know the effectiveness of both techniques, which will be measured by different parameters such as functional recovery, late morbidity, cosmetic result, which will enable us to formulate protocols and / or guidelines for therapeutic and rehabilitative management according to the technique that demonstrates superior effectiveness according to the aforementioned parameters. Method: We will proceed to the selection of the clinical histories of the post-operated patients for humeral shaft fracture operated by traumatologists of the institution. The medical records of the patients who meet the inclusion and exclusion criteria will be selected, the data will be recorded in a collection card that will include epidemiological profile, clinical evolution according to the Quick DASH Scale, late morbidity and cosmetic result, and then proceed to obtain the results through statistical analysis according to study objectives.